Sistem Printing Nirkabel Menggunakan Raspberry Pi - Veralisa Veralisa; Sherwin R.U.A. Sompie; Elia K. Allo (Jurnal Teknik Elektro dan Komputer, 2019)
Abstract — Wireless network is a field that is related to communication between computer devices without using cables. This network is in the form of infrared, bluetooth and WiFi which are often found on smarthphone devices and other equpment. The system that has been made utilizes a WiFi network on the Raspberry Pi as the connecting hardware between devices and CUPS as the connecting server between the printer and the device. This system can make it easier for users to print documents either from Laptop / PC or from Smarthphone without having to connect directly to the printer via cable. The design shows that the Raspberry Pi can communicate well between  and printers at the maximum distance of 25 meters without obstacles and 15 meters with obstacles.Keywords — CUPS; Printer; Raspberry Pi;  Wireless.  Abstrak — Jaringan Nirkabel adalah suatu bidang yang berkaitan dengan komunikasi antar piranti komputer tanpa menggunakan kabel. Jaringan ini berupa infrared, Bluetooth dan WiFi yang banyak dijumpai pada perangkat smartphone dan peralatan-peralatan lain. Sistem yang telah dibuat memanfaatkan jaringan WiFi pada Raspberry Pi sebagai hardware penghubung antar perangkat dan CUPS sebagai server penghubung antara printer dengan device. Sistem ini dapat mempermudah user dalam mencetak dokumen baik dari Laptop/PC maupun dari Smarthphone tanpa harus terhubung langsung ke printer melalui media kabel. Hasil perancangan menunjukkan Raspberry Pi dapat berkomunikasi dengan baik antara smartphone dan printer pada jarak maksimal 25 meter tanpa halangan dan 15 meter dengan halangan. Kata Kunci — CUPS; Printer; Raspberry Pi; Nirkabel.